2022
DOI: 10.1186/s12916-022-02653-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolomic profiling of dietary patterns associated with glucose metabolism status: The Maastricht Study

Abstract: Background Glucose metabolism has been reported to be affected by dietary patterns, while the underlying mechanisms involved remain unclear. This study aimed to investigate the potential mediation role of circulating metabolites in relation to dietary patterns for prediabetes and type 2 diabetes. Methods Data was derived from The Maastricht Study that comprised of 3441 participants (mean age of 60 years) with 28% type 2 diabetes patients by design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…They also found that three healthy dietary patterns (Alternative Healthy Eating Index (AHEI), the Dietary Approaches to Stop Hypertension (DASH) diet, and a Mediterranean-style (MDS) diet) shared a common metabolic profile of 24 lipids. Another study found that AHEI was linked to specific fatty acids that lowered the risk of cardiovascular diseases [ 68 ], while MDS and DASH influenced glucose metabolism through circulating metabolites, which suggest prevention strategies for T2DM [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also found that three healthy dietary patterns (Alternative Healthy Eating Index (AHEI), the Dietary Approaches to Stop Hypertension (DASH) diet, and a Mediterranean-style (MDS) diet) shared a common metabolic profile of 24 lipids. Another study found that AHEI was linked to specific fatty acids that lowered the risk of cardiovascular diseases [ 68 ], while MDS and DASH influenced glucose metabolism through circulating metabolites, which suggest prevention strategies for T2DM [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al found that following a healthy dietary pattern such as the Mediterranean diet or the Dietary Approaches to Stop Hypertension diet (DASH) may impact the glucose metabolism through circulating metabolites. This offers a new understanding of how diet influences the glucose metabolism and can help in developing strategies to prevent type 2 diabetes [ 187 ]. Additionally, a pattern characterized by higher levels of very-long-chain saturated fatty acids (VLCSFAs) and lower levels of alpha-linolenic acid (ALA) was linked to a healthier metabolic profile [ 188 ].…”
Section: Role Of Dietary Pattern On Metabolic Healthmentioning
confidence: 99%
“…This approach helps identify the molecular mechanisms of complex diseases, as well as for disease monitoring and risk assessment. In the past, targeted and untargeted metabolomics studies have been used to study the metabolome signature of obesity in response to dietary intake [ 20 ], the effects of specific dietary patterns or weight loss [ 21 , 22 ] or gain interventions, and body fat (%) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%